PENDIDIKAN ETIKA PANCASILA DALAM MATA KULIAH PENDIDIKAN PANCASILA DI PERGURUAN TINGGI: SEBUAH KAJIAN LITERATUR - Mulyadi Nugraha, Dadi; Supriyono, Supriyono; Abih Gumelar; Kurniawaty, Imas (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Moral degradation among students, ranging from academic plagiarism, ethical violations, intolerance, to corrupt behavior, indicates a value crisis that threatens the character of the nation. Pancasila Education as a mandatory curriculum course in higher education has a strategic position to internalize Pancasila ethics, but its implementation often gets trapped in cognitive-oriented learning. This study aims to examine the concept, position, learning strategies, and challenges of Pancasila ethics education in the Pancasila Education course at higher education institutions. The method used is a literature review of scientific articles in accredited national journals and relevant references published from 2018 to 2024, analyzed using content analysis techniques thru the stages of identification, selection, in-depth reading, and thematic synthesis. The study results show that: (1) Pancasila ethics is a value-based ethical system derived from the five principles and serves as a normative guideline for students' moral considerations; (2) the Pancasila Education course is the main vehicle for Pancasila ethics education, but its effectiveness depends on the learning design; (3) participatory learning strategies such as case studies, group discussions, project-based learning, and game-based learning thru educational board games have proven to be more effective in internalizing Pancasila ethics values compared to the expository approach; and (4) the challenges faced include digital disruption, a learning orientation that emphasizes knowledge over attitude, and the gap between understanding and ethical behavior. This study recommends transforming the Pancasila Education learning model toward a reflective, contextual, and experience-based ethical practice model.